Analisis Sikap Siswa Terhadap Mata Pelajaran Fisika di SMA Ferdy Ferry Putra Kota Jambi (UPEJ Unnes Physics Education Journal, 2019)
The purpose of this study was to determine the attitudes of students towards physics from the results of student attitudes description by using indicators of learning pleasure physics, an attractive tendency with physics and a career interest in physics at SMA Ferdy Ferry Putra Kota Jambi. This type of research is quantitative using survey research procedures with the instruments used are questionnaires. The subjects of this study were 125 students at SMA Ferdy Ferry Putra Kota Jambi. The results of the analysis obtained from indicators learning pleasure physics of the category are sufficient a percentage of 64%. The indicators of an attractive tendency with physics are categorized sufficient with a percentage of 72%. Indicators of a career interest in physics are sufficient categorized with a percentage of 68%. Based on these results, students at SMA Ferdy Ferry Putra Kota Jambihave sufficient attitudes towards science learning.